Impact of Organizational Culture on Business Performance and Sustainable Development: Evidence from Small and Medium Enterprises in Vietnam - Thuy, Le Thu; Tam, Phan Thanh (Journal of Cultural Analysis and Social Change, 2025)
This study investigates the role of organizational culture in shaping business performance and sustainable development among small and medium enterprises (SMEs) in Vietnam. This economic sector contributes substantially to national growth yet faces persistent challenges related to resource constraints and sustainability transitions. Grounded in the Resource-Based View, Institutional Theory, and Stakeholder Theory, the research develops a multidimensional structural model integrating internal capabilities and external institutional factors, including environmental practices, social responsibility, governance conditions, political influences, technological change, and tax policy. The model was refined through expert consultation with 30 economic management specialists and empirically validated using survey data from 875 SME managers across southern Vietnam. Confirmatory factor analysis and structural equation modeling (SEM) were employed to examine measurement validity and test hypothesized relationships. The findings reveal that organizational culture exerts the most substantial positive influence on business performance and also significantly contributes to sustainable development. External institutional factors demonstrate statistically significant but modest effects, indicating limited practical influence within transitional economic contexts. Technological change emerges as a meaningful driver of sustainable development and further strengthens the cultural impact through a positive moderating effect. Business performance also positively affects sustainability outcomes, underscoring the role of financial and operational capacity in enabling long-term sustainability investment. The model explains 36.7% of the variance in business performance and 34.7% of the variance in sustainable development. This study contributes to the literature by providing an integrated theoretical and empirical perspective on SME sustainability in emerging economies. It offers actionable insights for policymakers and enterprise leaders seeking to foster sustainable competitiveness.